Access to cardiovascular medicines in low- and middle-income countries: a mini review - Mark Amankwa Harrison; Afia Frimpomaa Asare Marfo; Augustine Annan; Daniel Nii Amoo Ankrah (BMC, 2023)
Abstract Background Many cardiovascular (CV) medicines are required for long term. However, with their limited resources, low- and middle-income countries (LMICs) may have challenges with access to cardiovascular medicines. The aim of this review was to provide a summary of available evidence on access to cardiovascular medicines in LMICs. Methods We searched PubMed and Google scholar for English language articles on access to cardiovascular medicines for the period 2010-2022. We also searched for articles reporting measures for challenges in access to CV medicines from 2007 to 2022. Studies conducted in LMICs, and reporting availability and affordability were included for review. We also reviewed studies reporting affordability or availability using the World Health Organisation/Health Action International (WHO/HAI) method. Levels of affordability and availability were compared. Results Eleven articles met the inclusion criteria for review on availability and affordability. Although availability appears to have improved, many countries did not meet the availability target of 80%. Between economies and within countries, there are equity gaps in access to CV medicines. Availability is lower in public health facilities than private facilities. Seven out of 11 studies reported availability less than 80%. Eight studies which investigated availability in the public sector reported less than 80% availability. Overall, CV medicines, especially combined treatments are not affordable in the majority of countries. Simultaneous achievement of availability and affordability target is low. In the studies reviewed, less than 1-53.5 days wages were required to purchase one month supply of CV medicines. Failure to meet affordability was 9-75%. Five studies showed that, on average 1.6 days' wages of the Lowest-Paid Government Worker (LPGW) was required to purchase generic CV medicines in the public sector. Efficient forecasting and procurement, increased public financing and policies to improve generic use, among others are measures for improving availability and affordability. Conclusions Significant gaps exist in access to cardiovascular medicines in LMICs, and in many low-and lower middle-income countries access to cardiovascular medicines is low. To improve access and achieve the Global Action Plan on non-communicable diseases in these countries, policy interventions must be urgently instituted.